In vitro and in vivo anti-malarial activity of plants from the Brazilian Amazon. (December 2015) - Lima, Renata; Rocha e Silva, Luiz; Melo, Marcia; Costa, Jaqueline; Picanço, Neila; Lima, Emerson; Vasconcellos, Marne; Boleti, Ana; Santos, Jakeline; Amorim, Rodrigo; Chaves, Francisco; Coutinho, Julia; et al.
Abstract Background The anti-malarials quinine and artemisinin were isolated from traditionally used plants (Cinchona spp. andArtemisia annua, respectively). The synthetic quinoline anti-malarials (e.g. chloroquine) and semi-synthetic artemisinin derivatives (e.g. artesunate) were developed based on these natural products. Malaria is endemic to the Amazon region wherePlasmodium falciparum andPlasmodium vivax drug-resistance is of concern. There is an urgent need for new anti-malarials. Traditionally used Amazonian plants may provide new treatments for drug-resistantP. vivax andP. falciparum . Herein, the in vitro and in vivo antiplasmodial activity and cytotoxicity of medicinal plant extracts were investigated. Methods Sixty-nine extracts from 11 plant species were prepared and screened for in vitro activity againstP. falciparum K1 strain and for cytotoxicity against human fibroblasts and two melanoma cell lines. Median inhibitory concentrations (IC50 ) were established against chloroquine-resistantP. falciparum W2 clone using monoclonal anti-HRPII (histidine-rich protein II) antibodies in an enzyme-linked immunosorbent assay. Extracts were evaluated for toxicity against murine macrophages (IC50 ) and selectivity indices (SI) were determined. Three extracts were also evaluated orally inPlasmodium berghei -infected mice. Results High in vitro antiplasmodial activity (IC50  = 6.4–9.9 µg/mL) was observed forAndropogon leucostachyus aerial part methanol extracts, Croton cajucara red variety leaf chloroform extracts, Miconia nervosa leaf methanol extracts, andXylopia amazonica leaf chloroform and branch ethanol extracts.Paullinia cupana branch chloroform extracts andCroton cajucara red variety leaf ethanol extracts were toxic to fibroblasts and or melanoma cells.Xylopia amazonica branch ethanol extracts andZanthoxylum djalma -batistae branch chloroform extracts were toxic to macrophages (IC50  = 6.9 and 24.7 µg/mL, respectively).Andropogon leucostachyus extracts were the most selective (SI >28.2) and the most active in vivo (at doses of 250 mg/kg, 71 % suppression ofP. berghei parasitaemia versus untreated controls). Conclusions Ethnobotanical or ethnopharmacological reports describe the anti-malarial use of these plants or the antiplasmodial activity of congeneric species. No antiplasmodial activity has been demonstrated previously for the extracts of these plants. Seven plants exhibit in vivo and or in vitro anti-malarial potential. Future work should aim to discover the anti-malarial substances present.